2021
DOI: 10.1051/ocl/2021035
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of different parts fromMoringa oleiferaregarding protein, lipid composition and extractable phenolic compounds

Abstract: Fatty acids, amino acids, as well as total phenolic content and antioxidant activities, were presented from Moringa oleifera different parts (whole seeds, kernels, coats, pods and leaves). The investigated parts were a good source of protein (29.2, 37.8, 11.9, 10.1 and 22.8 g/100 g for whole seeds, kernels, coats, pods and leaves, respectively) with isoleucine, leucine, arginine, glycine, glutamine and tyrosine as amino acids in sufficient amount to meet the nutritional needs. Moringa seeds are also rich in oi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 58 publications
0
9
1
Order By: Relevance
“…Although some accessions exceeded 20% protein, they were lower than the 24.90-30.36% of Pérez-Ángel et al (2020), 25.29% of Shih et al (2011), 26.9% of Díaz-Fuentes, (2019 and 32.06% of Mbailao et al (2014). Fejér et al (2019) and Owon et al (2021) reported 22.8% protein in dried moringa leaves. They identified amino acids such as tryptophan, valine, threonine, isoleucine, lysine, methionine, phenylalanine, histidine, leucine, arginine, glycine, alanine, serine, aspartic, glutamine, tyrosine, cysteine and proline which are necessary for the proper functioning of the organism.…”
Section: Proteinmentioning
confidence: 81%
See 2 more Smart Citations
“…Although some accessions exceeded 20% protein, they were lower than the 24.90-30.36% of Pérez-Ángel et al (2020), 25.29% of Shih et al (2011), 26.9% of Díaz-Fuentes, (2019 and 32.06% of Mbailao et al (2014). Fejér et al (2019) and Owon et al (2021) reported 22.8% protein in dried moringa leaves. They identified amino acids such as tryptophan, valine, threonine, isoleucine, lysine, methionine, phenylalanine, histidine, leucine, arginine, glycine, alanine, serine, aspartic, glutamine, tyrosine, cysteine and proline which are necessary for the proper functioning of the organism.…”
Section: Proteinmentioning
confidence: 81%
“…Higher than 10.74 and 11.48% (Valdez-Solana et al, 2015) and similar to 22.05% of Chan-Matú et al (2020), 22.42% of Sánchez-Machado et al (2010 and 22.8% Owon et al (2021). Although some accessions exceeded 20% protein, they were lower than the 24.90-30.36% of Pérez-Ángel et al (2020), 25.29% of Shih et al (2011), 26.9% of Díaz-Fuentes, (2019 and 32.06% of Mbailao et al (2014).…”
Section: Proteinmentioning
confidence: 83%
See 1 more Smart Citation
“…The extract solution is filtered by filter paper and then removed (70% ethanol) by using rotary evaporation at 45oC; after that, the dry extracted seeds are stored in the refrigerator for further analyses. Finally, all the chemicals used are obtained from chemistry department-Faculty of Science (Koya University, Kurdistan, Iraq) (Kwon et al, 2019, Araújo et al, 2020, Owon et al, 2021.…”
Section: Preparation Of Flours and Extraction Of Plant Seedsmentioning
confidence: 99%
“…M. oleifera leaves were also found to contain substantial amounts of total phenol, protein, calcium, potassium, magnesium, iron, manganese and copper (Owon et al 2021). M. oleifera leaves are also a good source of phytonutrients such as carotenoids, tocopherols and ascorbic acid (Mahato et al 2021).…”
mentioning
confidence: 99%